Neuromodulation for chronic pain. Issue 10289 (29th May 2021) - Knotkova, Helena; Hamani, Clement; Sivanesan, Eellan; Le Beuffe, María Francisca Elgueta; Moon, Jee Youn; Cohen, Steven P; Huntoon, Marc A
Summary: Neuromodulation is an expanding area of pain medicine that incorporates an array of non-invasive, minimally invasive, and surgical electrical therapies. In this Series paper, we focus on spinal cord stimulation (SCS) therapies discussed within the framework of other invasive, minimally invasive, and non-invasive neuromodulation therapies. These therapies include deep brain and motor cortex stimulation, peripheral nerve stimulation, and the non-invasive treatments of repetitive transcranial magnetic stimulation, transcranial direct current stimulation, and transcutaneous electrical nerve stimulation. SCS methods with electrical variables that differ from traditional SCS have been approved. Although methods devoid of paraesthesias (eg, high frequency) should theoretically allow for placebo-controlled trials, few have been done. There is low-to-moderate quality evidence that SCS is superior to reoperation or conventional medical management for failed back surgery syndrome, and conflicting evidence as to the superiority of traditional SCS over sham stimulation or between different SCS modalities. Peripheral nerve stimulation technologies have also undergone rapid development and become less invasive, including many that are placed percutaneously. There is low-to-moderate quality evidence that peripheral nerve stimulation is effective for neuropathic pain in an extremity, low quality evidence that it is effective for back pain with or without leg pain, and conflicting evidence that it can prevent migraines. In the USA and many areas in Europe, deep brain and motor cortex stimulation are not approved for chronic pain, but are used off-label for refractory cases. Overall, there is mixed evidence supporting brain stimulation, with most sham-controlled trials yielding negative findings. Regarding non-invasive modalities, there is moderate quality evidence that repetitive transcranial magnetic stimulation does not provide meaningful benefit for chronic pain in general, but conflicting evidence regarding pain relief for neuropathic pain and headaches. For transcranial direct current stimulation, there is low-quality evidence supporting its benefit for chronic pain, but conflicting evidence regarding a small treatment effect for neuropathic pain and headaches. For transcutaneous electrical nerve stimulation, there is low-quality evidence that it is superior to sham or no treatment for neuropathic pain, but conflicting evidence for non-neuropathic pain. Future research should focus on better evaluating the short-term and long-term effectiveness of all neuromodulation modalities and whether they decrease health-care use, and on refining selection criteria and treatment variables.